Influence of Mulching and N Fertilization on Moisture Conservation, Infiltration Characteristics and Productivity of Upland Rice under Rainfed Situations - R.K. Tomar,; R.K. Singh,; C.V. Singh,; R.N. Garg,; V.K. Gupta,; R.N. Sahoo,; D. Chakraborty,; Naveen Kalra, (Journal of Soil and Water Conservation, 2022)
Field studies were conducted at CRURRS, Hazaribag, Jharkhand during two rainy seasons with the objectives to find out the suitable rate, method of N application and mulching and their impact on soil infiltration characteristics, moisture conservation, crop growth and productivity of unbunded upland rice in rain fed ecosystem. Seven treatment combinations comprised 20, 35, 40 and 50 kg N ha-1, 2% urea spray and mulching (dust mulch and fresh ipomea leaves @ 4 Mg ha’') were tested. Results revealed that the application of ipomea leaves as mulch considerably increased (112.5%)the infiltration rate 3.4 emhr-1 compared to unmulched (1.6 cm hr-1) plots. Similarly, cumulative infiltration was also relatively higher in mulched (77.8 cm) compared to unmulched (72.5 cm) treatment. At all the growth stages, appreciably higher soil moisture content in the profile was recorded in mulched compared to unmulched plots. Crop growth and yield components improved considerably and significantly higher grain (1.79 Mg ha-1) as well as straw (2.52 Mg ha-1) yield was obtained with application of 50 kg nitrogen ha-1.